2021
DOI: 10.1101/2021.06.25.449880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precancer: Mutant clones in normal epithelium outcompete and eliminate esophageal micro-tumors

Abstract: Human epithelial tissues accumulate cancer-driver mutations with age1-7, yet tumor formation remains rare. The positive selection of these mutations argues they alter the behavior and fitness of proliferating cells8-10. Hence, normal adult tissues become a patchwork of mutant clones competing for space and survival, with the fittest clones expanding by eliminating their less-competitive neighbors9-12. However, little is known about how such dynamic competition in normal epithelia impacts early tumorigenesis. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Later studies discovered CH without driver mutations is highly prevalent ( Zink et al, 2017 ), raising the question whether CH is a pre-cancerous state. These observations raise the question whether these clonal expansions represent pre-cancer states, or if the enhanced clonality of a tissue is a characteristic of normal aging ( Brash, 2015 ; Colom et al, 2021 ).…”
Section: Cancer Driver Induction By Environmental Genotoxinsmentioning
confidence: 99%
“…Later studies discovered CH without driver mutations is highly prevalent ( Zink et al, 2017 ), raising the question whether CH is a pre-cancerous state. These observations raise the question whether these clonal expansions represent pre-cancer states, or if the enhanced clonality of a tissue is a characteristic of normal aging ( Brash, 2015 ; Colom et al, 2021 ).…”
Section: Cancer Driver Induction By Environmental Genotoxinsmentioning
confidence: 99%
“…It was found that tissues, such as skin, lung and oesophagus, that had a direct exposure to environmental carcinogenic factors (UV radiation, smoking and nutritional habits), or had a very high proliferation rate exhibited the highest mutation burden [18]. There is also some evidence that in certain situations mutant clones in normal epithelium can play an anti-tumorigenic role [19].…”
Section: Introductionmentioning
confidence: 99%
“…While cancer is a disease with genetic mutations at its root, additional cell and tissue dynamics may play a large role whether a cell with driver mutations may expand and progress into cancer. Intra-tissue clonal dynamics (Colom et al, 2021;Kakiuchi and Ogawa, 2021) or the immune system (De Visser et al, 2006) may prevent the outgrowths of cells with cancer driver mutations. And, often neglected, both the immune system and clonal dynamics could be altered by exposure to (genotoxic) environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies discovered CH without driver mutations is highly prevalent , raising the question whether CH is a pre-cancerous state. These observations raise the question whether these clonal expansions represent pre-cancer states, or if the enhanced clonality of a tissue is a characteristic of normal aging (Brash, 2015;Colom et al, 2021).…”
Section: Driver Mutations In Non-malignant Tissuementioning
confidence: 99%